MASIHKAH BARANG BEKAS DIMINATI MASYARAKAT YOGYAKARTA? - Amalia, Noor Anisa Rizki; Ma’ruf, Ahmad (Jurnal Ekonomi & Studi Pembangunan, 2009)
This research analyses the consumer purchases interest on the used goods in Pakuncen Klithikan Market. It aims to find out whether the quality of product, price and service affect the customer purchase interest significantly on the used goods by using t test individually or F test collectively. The study also conducts classical assumption test. Base on analysis which have been done result indicate that variable sum of the quality product significant influence on the consumer purchase because value of t statistic equal to 3,957 bigger than value of t tables equal to 0,000. For the variable price significant influence on the consumer purchase because value of t statistic equal to 5,463 bigger than value of t tables equal to 0,000. Variable service effect significant influence on the consumer purchase because value of t statistic equal to 3,667 bigger than value of t tables equal to 0,000.